Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Dương Hoàng Thanh Mai

Help me

Dương Hoàng Thanh Mai
28 tháng 10 2023 lúc 5:54

loading...  

tuan manh
28 tháng 10 2023 lúc 7:32

\(x+y-2\sqrt{x-1}-4\sqrt{y-2}+2=0\left(1\right)\) đk: \(x\ge1;y\ge2\)
Đặt: \(a=\sqrt{x-1};b=\sqrt{y-2}\left(2\right)\)
\(\Rightarrow a^2+b^2=x+y-3\Leftrightarrow x+y=a^2+b^2+3\left(3\right)\)
thay (2)(3) vào (1) ta có:
\(a^2+b^2-2a-4b+5=0\Leftrightarrow\left(a^2-2a+1\right)+\left(b^2-4b+4\right)=0\Leftrightarrow\left(a-1\right)^2+\left(b-2\right)^2=0\Leftrightarrow\left\{{}\begin{matrix}a-1=0\\b-2=0\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}a=1\\b=2\end{matrix}\right.\Leftrightarrow}\left\{{}\begin{matrix}\sqrt{x-1}=1\\\sqrt{y-2}=2\end{matrix}\right.\Leftrightarrow}\left\{{}\begin{matrix}x=2\\y=6\end{matrix}\right.\left(tm\right)}}\)

tuan manh
28 tháng 10 2023 lúc 7:36

\(a^2+b^2+3-2a-4a+2=0\Leftrightarrow\left(a^2-2a+1\right)+\left(b^2-4b+4\right)=0\Leftrightarrow\left(a-1\right)^2+\left(b-2\right)^2=0\)
\(\Leftrightarrow\left\{{}\begin{matrix}a-1=0\\b-2=0\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}\sqrt{x-1}=1\\\sqrt{y-2}=2\end{matrix}\right.\)\(\Leftrightarrow\left\{{}\begin{matrix}x=1\\y=6\end{matrix}\right.\)\(\left(tm\right)\)


Các câu hỏi tương tự
Dũng
Xem chi tiết
Nam Nguyễn
Xem chi tiết
Chúa hề
Xem chi tiết
UltimateFantasy
Dao Dao
Phùng Ái Nguyên
Phùng Ái Nguyên
Phùng Ái Nguyên
Hieu Pham
Hieu Pham